THE INFLUENCE OF "SHOPEE CRISTIANO RONALDO 9.9 " E-COMMERCE ADVERTISING ON STUDENTS' SHOPPING INTEREST IN SPECIAL REGION OF YOGYAKARTA - Hamzah, Ami; Adiprabowo, Vani Dias (Jurnal Ilmiah Ilmu Komunikasi Communique, 2023)
Various factors can influence a person's buying interest in using a product. One of the factors that can influence buying interest is the advertisement presented by the manufacturer. This study aims to find out how the effect of Shoope e-commerce advertising on purchase intention. The method used in this research is a quantitative method. Respondents in this study were 100 students studying in the Special Region of Yogyakarta. Data collection was carried out by distributing questionnaires in the form of a Likert scale. The questionnaires collected by the researcher tested the data using the validity and reliability tests used in this study to analyze the data. The results of the study show that e-commerce advertisements on Shoope have a partial and significant effect on the buying interest of students in the Special Region of Yogyakarta. It is proved by the results of the t-test that the significance value of the relationship between e-commerce advertising and buying interest is 0.000. These results indicate that sign (0.00) < 0.05 which indicates that e-commerce advertising has a partial and significant influence on the buying interest of students in the Special Region of Yogyakarta. Based on the research that has been done regarding the effect of e-commerce advertising on the buying interest of students in the Special Region of Yogyakarta. As we know, the function of advertising itself is to promote goods or services so that the audience knows the goods or services we have. Shopee has a very good advertising and promotion strategy. Like every month, on the same date, there will be a large-scale event to promote products or services at Shopee or Shopee in collaboration with top artists to voice the promotion.